A T-matrix many-particle theory for coherently coupled superlattice optics - Schmielau, T.; Pereira Jr., M.F.; Henneberger, K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The high- order Coulomb correlations described by T-matrix diagrams in both carrier occupation and polarization functions are studied here with a Keldysh- Green’s Functions formalism. Numerical applications for low dimensional semiconductor systems illustrate the relevance of the effects and their importance for realistic nonlinear optical spectra calculations. A frequency and momentum resolved numerical demonstration of the Mott transition at the T-matrix level is presented.